A lower Viséan (Carboniferous) brachiopod fauna from the eastern Alborz Mountains, northern Iran, and its palaeobiogeographical implications. (15th January 2016) - Qiao, Li; Falahatgar, Mostafa; Shen, Shu‐Zhong
Abstract: The brachiopods from the upper part of the Mobarak Formation at the Kiyasar section in the eastern Alborz Mountains, northern Iran, have been studied in detail. Fifteen species assigned to 13 genera of Strophomenida, Orthotetida, Orthida, Productida, Athyridida and Spiriferida are described. The fauna is determined as early Viséan in age based on the presence of Eomarginifera paucispinosa, Grandispirifer mylkensis and Unispirifer sp., and their associated foraminifers Uralodiscus, Paraarchaediscus, Glomodiscus and Endothyra, though taxa ranging through the Tournaisian–Viséan are also present. A comparison of its palaeogeographical affinities with other faunas show that the Alborz brachiopod fauna maintains strong Palaeotethyan affinities based on its general similarities with those of Eurasia, North America and Australia. This is suggestive of a prevailing oceanic current that circulated between the northern and southern shelf sea of the Palaeotethys Ocean, with which the warm‐water brachiopod taxa were widespread in the Palaeotethyan Realm through the early Viséan. Copyright © 2016 John Wiley & Sons, Ltd.